HEALTH CARE IN THE SURGICAL CENTER: PREVENTION OF HOSPITAL INFECTIONS - da Silva Santos, Samara; Gomes Viana, Amanda; Dorlamys de Lima Coutinho, Priscilla; Graziele Cardoso de Almeida, Débora; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
The surgical center being a propitious sector to develop different types of bacteria, makes the nurse in constant improvement based always on scientific nature, the continuing education as a practice of prevention must be developed by the CCIH in a strategic way, a set of actions between the entire team decreases in this control of infections, including the length of stay for this patient, as well as hospital costs increase with the length of stay.